Sunni-Shia Views of the Status of ‘Adalah's Companions of the Prophet - Mahasin Haikal Amanullah; Muhammad Adip Fanani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Hadith science is a science that is closely related to history. A hadith can be said to be authentic if it has the quality of continuous sanad and fair narrators. The problem is, in moving towards justice, there are striking differences between Sunnis and Shiites. Sunnis are of the view that all the companions of the Prophet must be 'just. So there is no need to doubt the hadith narrated by them. On the other hand, the Shiites consider that they all apostated after the death of the Prophet Muhammad and they died as infidels. As a result of this disbelief, the friends are automatically eliminated from being fair. Because the first condition for justice is Islam. Each of these two groups quoted many verses from the Koran and hadith to strengthen their arguments. This article will explain the polemic of the debate on the nature of justice between Sunnis and Shiites. Firstly by explaining the meaning of Companions, the views of the two groups, and finally criticizing the opinions and arguments used by the two groups above. This research uses the library research method by examining the opinions expressed by the ulama, including the interpretation of verses, hadith sharah, and the ijtihad of the fuqoha'.